2005
DOI: 10.1103/physreve.72.065101
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically anomalous roughness of admissible crack traces in concrete

Abstract: We study the roughness of postmortem cracks in concrete plates of different size. We find that the set of admissible crack paths exhibits an intrinsically anomalous roughness; nevertheless, any individual crack trace in concrete is essentially self-affine. We also find that both the local and the global amplitudes of crack traces are distributed according to a log-logistic distribution characterized by the same scaling exponent, whereas the mean-square width distribution is best fitted by the Pearson distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…0 21 . 0 3 ± = δ [36]. Further, it was found that under the uniaxial and radial compressions randomly folded thin sheets exhibit Poisson's expansion obeying a power-law behavior with the 7 universal Poisson's index 01 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…0 21 . 0 3 ± = δ [36]. Further, it was found that under the uniaxial and radial compressions randomly folded thin sheets exhibit Poisson's expansion obeying a power-law behavior with the 7 universal Poisson's index 01 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the folding phenomena are associated with a rich class of crumpling phenomena [3], which belong to a wider class of interfacial deformation phenomena [5]. Because of their biological and technological importance, the properties of randomly folded thin materials are now the subject of increasingly growing attention [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations